2021
DOI: 10.1186/s12893-021-01312-1
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuousness and recurrence related factors of ultrasound-guided microwave ablation in the treatment of benign thyroid nodules

Abstract: Objective Microwave ablation (MWA) is a minimally invasive technique for the treatment of benign thyroid nodules. The purpose of this study was to evaluate efficacy and safety of ultrasound-guided MWA in the treatment of benign thyroid nodules, and to find out the recurrence related factors, so as to provide reference for future clinical work. Methods This study retrospectively analyzed the patients who received ultrasound-guided MWA for benign thy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…Previous evidence has supported the negative correlation between the therapeutic efficacy of ablation and initial volume of nodules (22,23). Therefore, we further evaluated the effect of nodule volume on the efficacy of EA and MWA.…”
Section: Discussionmentioning
confidence: 93%
“…Previous evidence has supported the negative correlation between the therapeutic efficacy of ablation and initial volume of nodules (22,23). Therefore, we further evaluated the effect of nodule volume on the efficacy of EA and MWA.…”
Section: Discussionmentioning
confidence: 93%
“…7 Xia et al report contradictory data with a higher energy to volume ratio in the recurrence group (p<0,05) in his retrospective case series. 15 The energy deployment in our patients with recurrence might have been underestimated: Cysts are recorded with the volume prior to evacuation, which takes part at the beginning of the procedure. Once evacuated, the target volume has become smaller requiring a respectively smaller amount of energy for sufficient treatment of the remaining wall.…”
Section: Discussionmentioning
confidence: 96%
“…Wang et al found 16 recurrencies in their series of 94 patients representing a recurrence rate of 17 %, 7 resembling our own results of 19 % on a per-patient basis. In a more recently published paper, Xia et al found a recurrence rate of only 2,3 % using the same definition for recurrence as Wang et al 15 Under the term "recurrence", we summarized all unsatisfying outcomes of our patients, including regrowth of the treated nodule during ultrasound follow-up, recurrent symptoms and failure of reducing the nodule volume > 50 % within 6 months. This liberal definition led to a comparably large part of patients experiencing recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies exploring MWA for BTN have used fixed time points for follow up, commonly recording changes in volume and VRR at 1, 3, 6, and 12 months after ablation ( 23 , 27 , 28 ). However, in actual clinical practice, follow-up times are influenced by poor patient compliance and insufficient knowledge of the disease.…”
Section: Discussionmentioning
confidence: 99%